Developing environmentally friendly furniture through life cycle analysis / Kamarulzaman Nordin ... [et al.] - Nordin, Kamarulzaman; Jamaludin, Mohd Ariff; Ahmad, Mansur; Abd Jalil, Ashari (2004)
The furniture industry is one of Malaysia's mainstays in economy and had gain reputation in industrial sector ever since the introduction of the first Industrial Master Plan (1st IMP). It has emerged from craftsmen's traditions specializing in customized, one-off production towards standardized batch production, often aimed at an international market. With the current development on environmental issues, Malaysian furniture manufacturers that rely or planning to venture into export markets need to re-organize their business strategy to accommodate this issue in order to enable them to penetrate global market as well as staying ahead of their competitors. As such, product developers, manufacturers, material and equipment suppliers, and those linked to the furniture industry, as well as public authorities need to analyze the industry's environmental status and made suggestions for ecological improvement initiatives in important areas. This paper aimed to give an overview on the steps that can be taken towards the development of environmentally friendly furniture. The procedures generally founded on the life-cycle analysis approach which focused on the cradle-to-grave environmental impact. It embodies environmental issues in the product development process by minimizing negative environmental burdens in furniture design and manufacture while upholding other requirements of the products such as function, usability, maintenance and service life, aesthetics and economy.